Effect of Alkaline Activated Cashew Nut Shell Ash in the Stabilization of Weak Clayey Soil—An Experimental Study - Parthiban Devarajan; Dhanasingh Sivalinga Vijayan; Shanmuga Sundar Saravanabhavan; Arvindan Sivasuriyan; Naveen Sankaran; Theodoros Chrysanidis; Zineb Moujoud (Ceramics)
Weak clayey soils in construction are considered problematic due to their high compressibility and low bearing capacity. This study proposes an environmentally friendly replacement for conventional soil stabilizers through the use of geopolymer (GP) containing Cashew Nut Shell Ash (CNSA) to improve soil characteristics. In this study, the CNSAGP was compared with lime-stabilized soil for unconfined compressive strength (UCS), durability, and improved microstructure. The experimental outcomes showed that 9 M + CNSAGP with 4% CNSA provided a UCS of 1900 kPa, which was higher than the lime-stabilized soil (6% lime with 4% CNSA) at 1400 kPa. Durability test results revealed that the CNSAGP-treated sample had better protection against water damage with a strength loss of about 18%, while the lime-treated sample had a strength loss of about 25%. Thermal stability analysis showed that CNSAGP had lower LOI values compared to lime-stabilized samples (0.17% at 900 °C), which indicates CNSAGP’s heat resistance. Microstructure analysis revealed that CNSAGP-stabilized soil was less porous, the microstructure being denser because of reactions of aluminosilicate and pozzolanic activity. Moreover, it affected the soil’s alkalinity, making it better, and improved Atterberg limits, which affected the plasticity and workability. These findings show that CNSAGP is a long-lasting and eco-friendly means of soil stabilization with higher strength, thermal stability, and durability than traditional methods and can be used in engineering.